USATF's Women's Pole Vault World Wide Web Site USATF's Women's Pole Vault World Wide Web Site
This site is a world-wide non-profit resource for girl's and women's pole vaulting, established by USA Track & Field's Women's Pole Vault Development. Contents: The Olympics Add the Women's Pole Vault, High School Rankings, Senior Rankings, Junior Rankings, NCAA Div I Rankings, Records, Meets and Results, Pole Vaulting News, Women's Pole Vaulting Newsletter, Related Sites, Directory .